Olive Oil: Nutritional Applications, Beneficial Health Aspects and its Prospective Application in Poultry Production - Bilal, Rana M.; Liu, Chunjie; Zhao, Haohan; Wang, Yanzhou; Farag, Mayada R.; Alagawany, Mahmoud; Hassan, Faiz-ul; Elnesr, Shaaban S.; Elwan, Hamada A. M.; Qiu, Huajiao; Lin, Qian (Frontiers in Pharmacology, 2021)
Plant polyphenols have promoting health features, including anti-mutagenic, anti-inflammatory, anti-thrombotic, anti-atherogenic, and anti-allergic effects. These polyphenols improve the immune system by affecting the white blood cell proliferation, as well as by the synthesis of cytokines and other factors, which contribute to immunological resistance. Olive trees are one of the most famous trees in the world. Whereas, olive olive oil and derivatives represent a large group of feeding resource for farm animals. In recent years, remarkable studies have been carried out to show the possible use of olive oil and derivatives for improvement of both animal performance and product quality. In vivo application of olive oil and its derived products has shown to maintain oxidative balance owing to its polyphenolic content. Consumption of extra virgin olive oil reduces the inflammation, limits the risk of liver damage, and prevents the progression of steatohepatitis through its potent antioxidant activities. Also, the monounsaturated fatty acids content of olive oil (particularly oleic acid), might have positive impacts on lipid peroxidation and hepatic protection. Therefore, this review article aims to highlight the nutritional applications and beneficial health aspects of olive oil and its effect on poultry production.